Constitutionality of Formal Testing of Draft Laws by the Constitutional Court - Baharuddin Riqiey; Reza Maulana Hikam (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The Constitutional Court, as one of the state institutions regulated in the 1945 Constitution of the Republic of Indonesia, has the authority to test laws against the constitution. However, constitutional practice in Indonesia shows that there are tests of laws that have not been approved by the President or have not received a State Gazette number, which are still in the form of bills. This study aims to analyze the characteristics of laws as objects of testing in the Constitutional Court and the authority of the Constitutional Court in testing bills. The results of the study indicate that laws as statutory regulations are legal instruments that are stipulated under normal circumstances and can only be considered laws if they have gone through five stages: planning, drafting, discussion, ratification, and promulgation. Without fulfilling these stages, a text cannot be considered a binding law, so that testing in the Constitutional Court is not possible. The Constitutional Court only has the authority to test laws that have been passed, not bills against the 1945 Constitution of the Republic of Indonesia.